My doctor: dynamic scheduling and communication - Sirajee, Ashraf Hasan; Utsash, Masrur Masqub; Debi, Satabdi Rani (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.